TINJAUAN FIKIH MUAMALAH TERHADAP PENETAPAN DENDA PADA ARISAN ONLINE (STUDI KASUS NAGARI LIMA KAUM, KECAMATAN LIMA KAUM, KABUPATEN TANAH DATAR) - Latifah Siswati; Hidayati Fitri (UIN Mahmud Yunus Batusangkar, 2023)
The main problem in this study is the implementation of the online arisan fine contract in Nagari Limo Kaum reviewed in muamalah fiqh. This study aims to explain and analyze the implementation of online arisan fines in Limo Kaum. As well as explaining and analyzing how muamalah fiqh views the implementation of the online arisan fine contract in Nagari Limo Kaum.This research method is a field research, using a qualitative descriptive approach. As the main data source, namely the people involved in implementing online arisan practices in Nagari Limo Kaum, the data sources obtained included the admin and 5 members of the arisan who played along. Meanwhile, secondary data sources were obtained through a number of books, journals and other reading sources available. relation to the title of the researcher can provide additional information or data to strengthen the primary data.Based on the results of the research, it was found that the implementation of fines on online arisan is that the admin promotes a chain message which is then distributed via WhatsApp messages. As well as prospective members who are interested the admin will provide the requirements for an ID card or cellphone number that can be contacted. After all is collected the admin will form an arisan group, in carrying out the arisan the admin does not pay at all and only runs the arisan, if there is a delay in paying the arisan the admin will give a fine to members of 10 thousand for those who have not received it and 15 thousand for those who have received the arisan . Meanwhile, according to the muamalah fiqh review, the practice of fines like this is contrary to the principle of muamalah where muamalah must be carried out clearly and openly and using the principle of consensual and prioritizing willingness in every transaction. Meanwhile, fines collected are not notified to members where they are used and in what amount the fines received by the admin were also not explained so that there it was seen that the admin was not open to its members resulting in the penalty contract at the turning into a fasid or damaged contract and the contract being classified as a vanity contract.